ระบบจำลองการสร้างลายโครเชต์ - ณัฐวัตร ศิริประทุม (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Crochet patterns are very important for knitting. Nowadays, the most popular way to record crochet patterns is drawing with humans or using computer programs. When recording a crochet pattern to create a crochet diagram, only images that contain symbols are used, but errors may occur. We wanted to use a method that could more clearly and conveniently record the pattern drawing by using a string of English characters instead of the crochet symbols. Moreover, it changes the string to an image of the crochet chart for further use. The aforementioned reason is the origin of this project.